Case Study: Analysis of Work Breakdown Structure on Project Completion Time in the Procurement of Industrial Oleochemicals Items - Audrey Budiawan; Budi Husodo Bisowarno; Tedi Hudaya (Journal of Social Research, 2026)
This research aims to analyze the application of project management in the areas of procurement knowledge (procurement) and logistics in the production facility construction project at PT X, an oleochemicals industry located in Indonesia. The problem to be solved arises from deviations in time and cost, particularly in the delivery schedule of items packaged in containers and shipped from international ports to Indonesia. These deviations result in cost overruns due to logistics delay fines. This study employs a descriptive quantitative approach using comparative analysis techniques. Primary data include project schedule documents, logistics reports, and actual cost data. The results of the analysis show that the greatest deviation occurred in the customs clearance phase and in the handling of container-to-factory transportation. The effect of schedule deviation on cost deviation is examined in this paper, and after analysis, it is concluded that there is a need to enhance the effectiveness of project change management in the procurement process to formally mitigate and integrate logistics schedule changes, thereby controlling the risk of cost overruns.